A Re-evaluation of the Association Between Helicobacter pylori Infection and Pediatric Recurrent Abdominal Pain: A Systematic Review of Organic Versus Functional Etiologies - Rizqi Primasane Hariyani; Jauhari Tri Wasisto; Trini Handayani (The International Journal of Medical Science and Health Research, 2025)
Introduction: The association between Helicobacter pylori infection and Recurrent Abdominal Pain (RAP) in children is a subject of long-standing, significant controversy. While numerous studies in hospital-based settings report a significant link, major practice guidelines conclude no association exists for functional abdominal pain. This systematic review aims to resolve this conflict by synthesizing the evidence through the distinct frameworks of organic versus functional gastrointestinal disease. Methods: This review adheres to the PRISMA 2020 guidelines. A systematic search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library was conducted for studies published from 1995 to 2025. Observational (cross-sectional, case-control, cohort) studies, randomized controlled trials (RCTs), and meta-analyses comparing H. pylori-positive and H. pylori-negative pediatric patients (<18 years) with RAP or functional abdominal pain disorders (FAPDs) were included. Study quality was assessed using the Newcastle-Ottawa Scale (NOS) for observational studies. Results: Eighteen primary studies, including four meta-analyses, met the inclusion criteria. The evidence was highly stratified by study setting. A key meta-analysis demonstrated a statistically significant and strong association between H. pylori and abdominal pain in hospital-based studies (Pooled Odds Ratio 2.87; 95% Confidence Interval [CI]: 1.62–5.09). This was supported by hospital-based cohorts reporting that 100% of H. pylori-positive RAP patients had organic gastritis and 80% experienced symptom resolution post-eradication. Conversely, the same meta-analysis found no association in population-based studies (Pooled OR 0.99; 95% CI: 0.46–2.11). This null finding was confirmed by large, population-based studies  and meta-analyses specific to FAPDs like Irritable Bowel Syndrome (IBS), which found no significant link. Discussion: The "controversy" in the literature is identified as a "lumping fallacy," wherein studies fail to differentiate between two distinct clinical entities: (1) organic RAP caused by H. pylori-induced gastritis/PUD, and (2) true, Rome IV-defined FAPD, a disorder of gut-brain interaction. The significant findings (OR 2.87) represent the subset of children with organic disease, while the null findings (OR 0.99) represent the larger FAPD population where H. pylori is an incidental finding. Conclusion: The association between H. pylori and pediatric RAP is significant, but only within the specific subgroup of children whose pain is a clinical manifestation of H. pylori-driven organic gastroduodenal pathology. H. pylori infection is not associated with true functional abdominal pain. Clinical practice must, therefore, be guided by rigorous triage using "red flag" symptoms to differentiate patients who require organic workup (including H. pylori testing) from those who require FAPD management.